2017
DOI: 10.1002/mar.21019
|View full text |Cite
|
Sign up to set email alerts
|

Under the sway of a mobile device during an in‐store shopping experience

Abstract: Mobile device technology is transforming the retail shopping experience. Today's consumers are mobile dependent, preferring to consult with their phone, instead of using the salesperson, while shopping at the retail store. In the absence of literature investigating how the salesperson might sell to this omni‐channel, mobile‐connected consumer, this paper proposes a conceptual model and tests its proposed linkages. The empirically tested model presents a dyadic view of the omni‐channel consumer and the salesper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 112 publications
(176 reference statements)
1
61
0
1
Order By: Relevance
“…Recently, the boundaries between channels have blurred and customers use them seamlessly and simultaneously during their purchase experiences (Verhoef et al, 2015). The concept of webrooming can thus be extended as a form of omnichannel shopping where the consumer searches for information online before going to the physical store to make the purchase and also access the internet with their smartphones while in store to search for information (Rippé et al, 2017).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Recently, the boundaries between channels have blurred and customers use them seamlessly and simultaneously during their purchase experiences (Verhoef et al, 2015). The concept of webrooming can thus be extended as a form of omnichannel shopping where the consumer searches for information online before going to the physical store to make the purchase and also access the internet with their smartphones while in store to search for information (Rippé et al, 2017).…”
Section: Research Backgroundmentioning
confidence: 99%
“…The nature of mobile devices, their physical characteristics and their size allow customers to search and shop anywhere and at any time (Gao et al, 2015;Rodríguez-Torrico et al, 2017). Today's consumers prefer to consult with their phones rather than interact with a salesperson while shopping at the store (Rippé et al, 2017). Thus, customers usually use their own devices in stores to search for more information about a product by scanning QR codes, comparing products, checking product ratings and asking for advice (Shankar, 2014;Verhoef et al, 2015;Voropanova, 2015).…”
Section: Role Of Customer's Own Devicesmentioning
confidence: 99%
“…In their study on how companies are leveraging digital technologies with the aim of transforming the customer experience, Parise et al (2016) found that "72 per cent of consumers said that a relevant mobile offer delivered to their smartphone while shopping in a store would significantly influence their likelihood to make a purchase." Likewise, Kim and Hahn (2015) determined that consumer adoption of mobile technology increased future purchase intention, whereas Rippé et al (2017) more specifically demonstrated that in-store mobile searches are positively related to in-store purchase intention.…”
Section: Role Of Customer's Own Devicesmentioning
confidence: 99%
“…In this new scenario, the smartphone has become a powerful tool. Customers are mobile dependent and prefer to consult their phones rather than salespersons to carry out different tasks in-store, such as searching for product information and prices, checking product ratings, comparing products, and paying; they also use them to consult family and friends for advice [2][3][4]. Moreover, they have the potential to become important drivers in the omnichannel context due to their importance as initiators for conversion to other touchpoints or channels.…”
Section: Introductionmentioning
confidence: 99%